Concussion Evaluation and Management in Pediatrics. Issue 2 (March 2015) - Rivera, Robin G.; Roberson, Susan P.; Whelan, Margaret; Rohan, Annie
<x xml:space="preserve">Abstract</x> Abstract Concussions are among the most complex injuries to assess and manage in sports medicine and primary care. Sports concussion in youth has received much attention in recent years because research shows that improperly managed concussion can lead to long-term cognitive deficits and mental health problems. There are several notable risk factors affecting the incidence and severity of concussion in school-age children and adolescents, including a history of a previous concussion. A more conservative approach for return to activities following concussion has been proposed for children and adolescents. Programs of individualized, stepwise increases in physical activity have largely replaced use of algorithms for assigning a grade and activity expectations to concussions. Although validity and reliability testing is ongoing to support use of concussion assessment instruments in pediatric patients, it is practical and appropriate that clinicians incorporate symptom checklists, sideline and balance assessment tools, and neurocognitive assessment instruments into their practice in accordance with evidence-based guidelines.